The impeachment report : the House Intelligence Committee's report on its investigation into Donald Trump and Ukraine (Broadway Books, 2019)
"The official report from the House Intelligence Committee on Donald Trump's secret pressure campaign against Ukraine, featuring an exclusive introduction by Pulitzer Prize-winning author and biographer Jon Meacham. For only the fourth time in American history, the House of Representatives has conducted an impeachment inquiry into a sitting United States president. This landmark document details the findings of the House Intelligence Committee's historic investigation of whether President Donald J. Trump committed impeachable offenses when he sought to have Ukraine announce investigations of former vice president Joe Biden and his son Hunter. These pages offer an account of the president's attempts to use the powers of his office to solicit foreign interference on his behalf in the 2020 election; and his subsequent attempts to obstruct the House investigation into his actions" --